2010
DOI: 10.1002/jls.20177
|View full text |Cite
|
Sign up to set email alerts
|

Increasing transformational leadership by developing leaders' information‐processing systems

Abstract: According to the cognitive-experiential self theory (CEST), all behavior is guided by two informationprocessing systems: the rational system and the experiential. Previous research with school leaders has shown that the rational system and constructive elements of the experiential system have a strong positive relationship with transformational leadership, as outlined in the Full-Range Leadership Theory. This article reports a pretest, posttest study using an intervention and control group to test whether chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…In a number of recent studies, connections have been found between individual differences in information‐processing styles, as conceptualized in CET, and leadership styles, leadership behaviors, and related outcomes (e.g., Atwater & Yammarino, ; Cerni et al, ; Cerni, Curtis, & Colmar, , , , , ; Curtis & Lee, ; Dubinsky, Yammarino, & Jolson, ; Humphreys & Zettel, ). These findings were a source of inspiration to develop the Cognitive‐Experiential Leadership Model.…”
Section: Cognitive‐experiential Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…In a number of recent studies, connections have been found between individual differences in information‐processing styles, as conceptualized in CET, and leadership styles, leadership behaviors, and related outcomes (e.g., Atwater & Yammarino, ; Cerni et al, ; Cerni, Curtis, & Colmar, , , , , ; Curtis & Lee, ; Dubinsky, Yammarino, & Jolson, ; Humphreys & Zettel, ). These findings were a source of inspiration to develop the Cognitive‐Experiential Leadership Model.…”
Section: Cognitive‐experiential Theorymentioning
confidence: 99%
“…A limitation of the studies cited here that connect CET information‐processing styles and leadership is that the results cannot demonstrate a causal connection between information‐processing style and leadership style, as these studies used correlational designs. In response to the limitation an intervention study using an experimental design was undertaken to determine if a causal relationship existed between CET information‐processing and transformational leadership (Cerni et al, , ).…”
Section: The Cognitive‐experiential Leadership Modelmentioning
confidence: 99%
“…This figure shows that those observed to have increased their psychological wellbeing the most over the intervention period tend to be most closely connected to those that received coaching as measured through closeness centrality in the coachee neighbourhood network. improvement in transformational leadership measures (Grant et al 2010a;Cerni et al 2010). It is important to note that the improvements in transformational leadership were identified by others and not via self-report.…”
Section: Discussionmentioning
confidence: 95%
“…Research on coaching at the individual level has been related to: increased goal striving, hope and wellbeing (Green et al 2006); increases in goal commitment, attainment and environmental mastery (Spence and Grant 2007); increases in cognitive hardiness, mental health and hope (Green et al 2007); the reduction of workplace stress and anxiety (Gyllensten and Palmer 2005); improvements in transformational leadership (Grant et al 2010a;Cerni et al 2010); and the enhancement of outcome expectancies and self-efficacy (Evers et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…There are a limited number of empirical studies exploring the role of self‐attention in the leader development process (e.g., Cerni, Curtis, & Colmar, ; DeRue, Nahrgang, Hollenbeck, & Workman, ; Hannah, ), with results indicating that self‐attention may be important in facilitating leader development. Cerni et al () developed a 10‐week coaching intervention to increase conscious awareness of automatic information‐processing systems, in a sample of Australian school principals. The purpose of these coaching sessions was to facilitate conscious reflections on professional practice as a principal/teacher, with a focus on questioning thought processes, and applying positive thinking, self‐acceptance, and analytical reasoning to these reflections.…”
Section: Defining Leader Developmentmentioning
confidence: 99%